The influence of investment decisions and stock prices on company value with profitability as a moderating variable - Arifin, Muhammad Rais; Munandar, Agus (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to analyze the effect of investment decisions and stock prices on the company value in the infrastructure sector, moderated by profitability. The study uses multiple linear regression to examine the relationships between variables, with secondary data obtained from the financial statements of infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the period of 2018-2021. The independent variables used in this study are investment decisions, measured by the Price Earnings Ratio (PER), stock price, measured by closing share price, and profitability, measured by Return on Equity (ROE). The dependent variable is company value, measured by Price to Book Value (PBV). The results of the study show that investment decisions and stock prices have a positive and significant effect on company value. However, profitability does not moderate the relationship between investment decisions and stock prices on company value. The implications of this study’s findings suggest that infrastructure companies should pay attention to investment decisions and strategies that can influence stock prices, as both have a significant impact on increasing company value. Additionally, although profitability does not moderate the relationship, companies should still maintain profitable performance to ensure the sustainability of healthy operations.